1991
DOI: 10.1097/00006123-199103000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of recombinant tissue plasminogen activator-induced thrombolysis in the central nervous system and systemic arteries

Abstract: Recombinant tissue plasminogen activator (rTPA) has been more effective in inducing thrombolysis in laboratory studies of intracranial thrombosis than clinical studies of systemic or coronary thrombosis would indicate. To evaluate this discrepancy, 21 rabbits were subjected to embolic occlusion of the right internal carotid artery (ICA) by retrograde injection of a tin-tagged, 2-hour-old autologous clot through the external carotid artery with angiographic monitoring in the same manner as in a previously repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, there is mounting evidence that the cerebral endothelial cells respond differently to the presence of TPA compared with their peripheral counterparts, de Bono et al 37 showed that TPA-induced cerebral bleeding as a result of injury was inhibited with tranexamic acid, whereas aprotinin was more potent in reducing peripheral bleeding times. Further evidence was presented by Chehrazi et al, 33 who showed TPA to be more potent at lysing equivalent clots in the central nervous system compared with clots in the peripheral vasculature. Thus, the reason for reduced cerebral hemorrhages may be more complicated than simply attenuating circulating plasmin levels.…”
mentioning
confidence: 87%
“…However, there is mounting evidence that the cerebral endothelial cells respond differently to the presence of TPA compared with their peripheral counterparts, de Bono et al 37 showed that TPA-induced cerebral bleeding as a result of injury was inhibited with tranexamic acid, whereas aprotinin was more potent in reducing peripheral bleeding times. Further evidence was presented by Chehrazi et al, 33 who showed TPA to be more potent at lysing equivalent clots in the central nervous system compared with clots in the peripheral vasculature. Thus, the reason for reduced cerebral hemorrhages may be more complicated than simply attenuating circulating plasmin levels.…”
mentioning
confidence: 87%
“…Further, there is experimental data suggesting that rt-PA is more effective in inducing thrombolysis within precerebral vessels than systemic vessels [ 21 ]. At present, IV rt-PA at 0.9 mg/kg is licensed in many countries and appears to represent best practice and other drugs (see new thrombolytics below), doses or routes of administration should only be used in randomised controlled trials [ 22 ].…”
Section: Preclinical Trials Of Rt-pamentioning
confidence: 99%